Analisis Pengaturan Label Halal Terhadap Produk yang Beredar di Indonesia - Oktaviana Hardayanti Adismana (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to analyze the qualifications of violating Article 26 Paragraph (2) of the Law on Halal Product Guarantee and the probability of criminal prosecution of violations of Article 26 Paragraph (2) of the Law on Halal Product Guarantee whether or not it can be carried out. The research method is normative research, data collection techniques use library research, and data analysis is descriptive-analytical with a qualitative approach. The study results show that the qualification for violating Article 26 Paragraph (2) of the Law on Halal Product Guarantee is an administrative violation with provisions for administrative sanctions in the form of a verbal warning, written warning, or administrative fine. Then the violation is not included as a criminal offence with the criminal sanctions provisions in Article 10 of the Criminal Code. In the future, legislators hope to take actionIviolationIobligationIbusinessmenIincludeIdescriptionInoIhalalIonIproductImade fromIharam, with stricter sanction provisions in the form of criminal sanctions. Criminal sanctions are needed as a preventive effort to avoid the possibility that business actors will violate their obligations or repeat their actions. The possibility of criminal prosecution for violations of Article 26 Paragraph (2) of the Halal Product Guarantee Law may be possible because such violations constitute unlawful acts and are also acts prohibited in Article 8 Paragraph (1) Letter i of the Consumer Protection Law by imposing criminal sanctions in the form of imprisonment or fines. Criminal prosecution for violations of Article 26 paragraph (2) of the Law on Halal Product Guarantee needs to be carried out by regulating the provisions on criminal sanctions but does not eliminate the provisions on administrative sanctions in Article 27 paragraph (2) of the Law on Guarantee of Halal Products. PenaltyIcriminallusedlaslthe last remedy, lastlusedlwhenlsuspectedlpenaltyladministrativelonlChapterl27lsentencel (2) LawlGuaranteelProductlHalallwhichlalreadylappliedlnoleffectivelforlcopelcrime basedlconsiderationljudge